Advances in cement analysis and concrete petrography - Cong, Derek; Broton, Don (ASTM International, 2019)
"Contains peer-reviewed papers that were presented at a symposium held June 27, 2018, in San Diego, California, USA. The symposium was sponsored by ASTM International Committee C01 on Cement and Subcommittee C01.23 on Compositional Analysis."
Keywords: Concrete -- Analysis.; Concrete -- Defects.; Cement -- Additives.; Petrology.; elektronické knihy; electronic books